Predicting Icebreaking Capabilities of Icebreakers - Lewis, Jack W.; Edwards, Roderick Y., Jr (1969)
This document describes various methods for predicting the icebreaking capabilities of icebreakers with conventional hull forms. The influence of various ship parameters upon icebreaking capability is discussed. The effect of the characteristics of ice upon the ramming and continuous icebreaking capability of icebreakers is investigated. The report includes a comprehensive list of mathematical techniques for predictions of ramming mode and continuous mode icebreaking capability. It contains a development of scaling procedures for model tests involving the interaction of a ship type vehicle and a floating ice sheet. A section is included which presents the results of full scale and model tests of icebreakers sponsored by the U. S. Coast Guard. Using the mathematical techniques recommended in this report, the performance of many existing icebreakers is analyzed and presented. (Author)